Protection Induced by Vaccination with Recombinant Baculovirus and Virus-like Particles Expressing Toxoplasma gondii Rhoptry Protein 18 - Keon-Woong Yoon; Ki-Back Chu; Hae-Ji Kang; Min-Ju Kim; Gi-Deok Eom; Jie Mao; Su-Hwa Lee; Md Atique Ahmed; Fu-Shi Quan (Vaccines, 2022)
Heterologous immunization is garnering attention as a promising strategy to improve vaccine efficacy. Vaccines based on recombinant baculovirus (rBV) and virus-like particle (VLP) are safe for use, but heterologous immunization studies incorporating these two vaccine platforms remain unreported to date. Oral immunization is the simplest, most convenient, and safest means for mass immunization. In the present study, mice were immunized with the Toxoplasma gondii rhoptry protein 18 (ROP18)-expressing rBVs (rBVs-ROP18) and VLPs (VLPs-ROP18) via oral, intranasal, and intramuscular (IM) routes to evaluate the protection elicited against the intracellular parasite T. gondii ME49 strain. Overall, boost immunization with VLPs-ROP18 induced a significant increase in T. gondii-specific antibody response in all three immunization routes. Parasite-specific mucosal and cerebral antibody responses were observed from all immunization groups, but the highest mucosal IgA response was detected from the intestines of orally immunized mice. Antibody-secreting cell (ASC), CD8+ T cell, and germinal center B cell responses were strikingly similar across all three immunization groups. Oral immunization significantly reduced pro-inflammatory cytokine IL-6 in the brains as well as that by IN and IM. Importantly, all of the immunized mice survived against lethal challenge infections where body weight loss was negligible from all three immunizations. These results demonstrated that protection induced against T. gondii by oral rBV-VLP immunization regimen is just as effective as IN or IM immunizations.